An archival controlled vocabulary for university archives: the experience of VTArq (UNESP, Brazil) - Moreira, Walter [UNESP]; Lopes Fujita, Mariangela Spotti [UNESP]; Piovezan dos Santos, Luciana Beatriz [UNESP] (Univ Zaragoza, 2016)
The experience of construction of a controlled vocabulary for processing the university records of the Universidade Estadual Paulista (UNESP VTArq) is presented. First, the different units of the university were consulted for the identification and collection of the expressions effectively used for representing the documentation. Thereafter, the adequacy of the vocabulary was assessed with the help of terminology management software. The experience shows the need of vocabulary specificity and standardization to support the organization and retrieval of information in the field of university archives.
Keywords: Thesauri; Planning; Construction; Archival science; Record management; University archives